Teaching academic writing : a toolkit for higher education - Coffin, Caroline; Coffin, Caroline, 1958-; Curry, Mary Jane; Goodman, Sharon; Hewings, Ann; Lillis, Theresa M.; Swann, Joan (London : Routledge, 2003)
"The authors explore a wide variety of text types from essays and reflective diaries to research projects and laboratory reports. The book draws on recent research in the fields of academic literacy, second language learning and linguistics. It is grounded in recent developments such as the increasing diversity of the student body, the use of the Internet, electronic tuition, and issues related to distance learning in an era of increasing globalisation."--Jacket
Issues in academic writing in higher education / Mary Jane Curry and Theresa M Lillis -- Approaches to teaching writing / Mary Jane Curry and Ann Hewings -- Writing for different disciplines / Caroline Coffin and Ann Hewings -- Planning the assessment of student writing / Sharon Goodman and Joan Swann -- Giving feedback on student writing / Theresa M Lillis and Joan Swann -- Academic writing in an electronic environment / Caroline Coffin and Sharon Goodman.
Includes bibliographical references and index.
Keywords: Academic writing -- Study and teaching; English language -- Rhetoric -- Study and teaching